(untitled) (Sunari Penjor : Journal of Anthropology, 2025)
This research aims to examine the background of the implementation of the Mengkurak Tulan traditional ceremony and its process. Mengkurak Tulan is a form of respect for parents. The approach used in this research is qualitative with a descriptive approach. Data collection techniques include observation, interviews, and documentation. The data analysis technique involves data collection, data reduction, data presentation, and drawing conclusions. This research employs Clifford Geertz’s Symbolic Interpretive theory. The Symbolic Interpretive theory will explore the meanings of each tool and activity during the event’s implementation. The results of this research indicate that this ceremony is rarely conducted because it requires a lot of preparation. There are two main reasons behind the implementation of the Mengkurak Tulan traditional ceremony: one being the joy felt by the family throughout their lives, and the other being families that experience difficulties or misfortunes. Through this event, they believe it serves as a remedy to heal their misfortunes. Many symbols are used throughout the event, from the beginning to the end. All activities and tools utilized certainly convey meanings that are believed by the Pakpak ethnic group to have specific values.